Non-Performing Loan, Loan to Deposit Ratio, Capital Adequacy Ratio dan Profitabilitas Bank: Peran Moderasi Ukuran Bank - Agung Prayogi (CV. Denasya Smart Publisher, 2024)
Bank profitability is a signal sent to bank stakeholders about bank performance over a certain period in the form of ratio, one of which is ROA. This research aims to find out the influence of NPL, LDR, CAR and the size of the bank on ROA. In addition, to know bank size as a moderation in the impact of the NPL, LDR and CAR on the ROA, the design of the research uses a quantitative approach. The research population is the entire Regional Development Bank in Indonesia of 31 banks. The samples were taken using purposive sampling, which produced 24 banks as samples. Data analysis techniques use double linear regression and Moderated Regression Analysis. The findings of this study explain that increased NPL ratio and bank size lead to lower ROA, increased LDR and CAR lead to higher ROA and the size of banks moderate the influence of NPL, LDR, and CAR on ROA. These results have implications for the Regional Development Bank in Indonesia to manage the risk profile, capitalization, and size of the bank as they affect ROAs. Moreover, stakeholders should also consider these factors when evaluating bank performance before investing.